Gender inclusive intermediary education, financial stability and female employment in the industry in Sub-Saharan Africa - Simplice Asongu; Yann Nounamo; Henri Njangang Ndieupa; Sosson Tadadjeu (African Governance and Development Institute (AGDI), 2021)
The study examines how financial stability modulates the effect of inclusive intermediary education on female employment in the industry for the period 2008-2018 in Sub-Saharan Africa. The empirical evidence is based on Tobit, Ordinary Least Squares (OLS) and Quantile regressions. There are positive interactive or conditional effects between inclusive intermediary education and financial stability in the Tobit, OLS and bottom quantiles estimations. A net positive (negative) effect is apparent in the 10th quantitle (median) of female employment in the industry distribution. Implications are discussed.
Keywords: E23; F21; F30; L96; O55; 330; inclusive education; financial sustainability; gender economic inclusion